Increasing Purchase Intention for Social Enterprise Product Through Re-Designing Product Packaging with Neuromarketing Approach (Case study: Cireundeu Indigenous Community) - Timothy Andrianus Philemon; Maria Widyarini; Paulina Kus Ariningsih; Riarni Adina Ardanareswari (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Abstract. The primary purpose of this paper is to explore how redesigning product packaging can increase customer purchase intention. The uniqueness of this research is the use of neuromarketing principles in redesigning product packaging, and the context that will be discussed is a social enterprise product. The methods used are mixed methods consisting of qualitative methods, experimental design, and quantitative methods. The principle of neuromarketing discussed in this study is eye-tracking. The quantitative research will then test the relationship between product packaging and purchase intention. A new packaging design was created for RASI product. For a long time, RASI (Beras Singkong or Cassava Rice) has been an iconic product for Cireundeu due to its heritage and unique culture. The eye-tracking experiments strongly correlate the new packaging design and product purchase intention. This article resulted in a new packaging design by applying the neuromarketing principle in a social setting.Keywords: Design, product packaging, neuromarketing, purchase intention, social enterpriseAbstrak. Tujuan utama dari penelitian ini adalah untuk mengeksplorasi bagaimana mendesain ulang kemasan produk dapat meningkatkan niat beli dari pelanggan. Keunikan penelitian ini adalah penggunaan prinsip neuromarketing dalam mendesain ulang kemasan produk, dan konteks yang akan dibahas adalah produk kewirausahaan sosial. Metode yang digunakan adalah metode campuran yang terdiri dari metode kualitatif, desain eksperimen, dan metode kuantitatif. Prinsip neuromarketing yang dibahas dalam penelitian ini adalah eye-tracking. Penelitian kuantitatif kemudian akan menguji hubungan antara kemasan produk dengan niat beli. Desain kemasan baru diciptakan untuk produk RASI. Untuk waktu yang lama, RASI (Beras Singkong) telah menjadi produk ikonik dari Kampung Adat Cireundeu. Eksperimen pelacakan mata sangat berkorelasi dengan desain kemasan baru dan niat pembelian produk. Artikel ini menghasilkan desain kemasan baru dengan menerapkan prinsip neuromarketing dalam lingkungan sosial.Kata kunci: Desain, kemasan produk, intensi membeli, kewirausahaan sosial, eye-tracking